Obesity and early-onset colorectal cancer risk: emerging clinical evidence and biological mechanisms - Xu, Peng; Tao, Zuo; Yang, Hua; Zhang, Cheng (Frontiers in Oncology, 2024)
Early-onset colorectal cancer (EOCRC) is indicated as a global burden. EOCRC The disease is associated with specific molecular and clinical features. As Obesity is a well-known risk factor for colorectal cancer, although its the role of obesity in EOCRC is still debated. This review is to explores the distinct role of obesity in EOCRC. This study review suggested obesity accelerated accelerates the progression of EOCRC progression and is correlated with a worse prognosis compared with late-onset colorectal cancer (LOCRC). This effect could be explained by metabolic disorders, dysbiosis of the intestinal flora, and obesity-induced inflammation. A better understanding The role of obesity in EOCRC is urged needs to be explored; in fact and obesity may be a potential factor in the prevention of EOCRC. Abstract：Early-onset colorectal cancer (EOCRC) is defined as diagnosed age at younger than 50 years of age and indicating indicates a health burden globally. EOCRC patients Patients with EOCRC have distinct risk factors, clinical characteristics, and molecular pathogenesis compared with older patients with CRC. Further investigations have identified different roles of obesity between EOCRC and late-onset colorectal cancer (LOCRC). As most Most studies concentrated have focused on the clinical characteristics of obesity in EOCRC, therefore, the insight mechanism of involved in the association between obesity and EOCRC remains inconclusive. Based on multiple studies in the literature, this This review demonstrated further states that obesity affects the carcinogenesis of EOCRC as well as its development and progression, which may result in lead to obesity-related metabolic syndrome, intestinal dysbacteriosis, and intestinal inflammation.